LITERATURE REVIEW: ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL VOLUME BANGUN RUANG DI KELAS V SEKOLAH DASAR - Putri Fahmi, Fadhila; Sofiah, Iffatus; Masniladevi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This literature review study aims to analyze the various difficulties faced by fifth-grade elementary school students in solving problems related to the volume of three-dimensional shapes. Mathematics is an important subject but is often considered difficult by students, especially in three-dimensional geometry. Through a review of various literature sources including books and scientific journals from 2020 onwards, it was found that student difficulties stem from internal and external factors. Internal factors include weak conceptual understanding, low spatial ability, and lack of learning motivation. External factors include less varied teaching methods, limited learning media, and an unconducive learning environment. The results of the study indicate that students' main difficulties lie in the stages of understanding the concept of volume, applying formulas, and interpreting word problems. The resulting recommendations include the use of concrete media, problem-based learning approaches, and strengthening the understanding of basic three-dimensional shape concepts before entering volume calculations.